Rancang Bangun Game Edukasi 2D Pengenalan Buah-Buahan Berbasis Android Menggunakan Metode Game Development Life Cycle (GDLC) - Tito Surya; Tommy Bustomi; Farindika Metandi (Riau Jurnal Teknik Informatika, 2026)
Technological developments have brought significant changes to the field of education, including early childhood education. However, there are still many learning methods that are less effective in attracting early childhood students’ interest in learning, especially in the digital era through fruit recognition game applications. Based on these issues, the problem formulation in this study is how to design and develop an engaging and interactive 2D educational game for fruit recognition aimed at early childhood learners. This study uses the Game Development Life Cycle (GDLC) method, which consists of six stages: initiation, pre-production, production, testing, beta, and release. The game was developed using Construct 2 and is intended for Android devices to make it easily accessible for early childhood users. The purpose of this study is to create an enjoyable and effective learning medium for early childhood children to learn fruit recognition while increasing learning interest through interactive digital media. The result of this study is the creation of an educational game that can be used as an alternative learning medium, helping early childhood children recognize various types of fruits in a fun, interactive, and more engaging way. Black box testing showed that all features functioned successfully, and beta testing involving teachers and the school principal obtained an average score of 89%, placing the game in the “very feasible” category as a fruit-recognition learning medium.